Palladium-catalyzed allylic etherification of phenols with vinyl ethylene carbonate - Lin, Shibo; Zhao, Xiaotian; He, Lihui; Li, Xuanhao; Jiang, Qian; Xiang, Lan; Ye, Yongqin; Gan, Xiaohong (Frontiers in Chemistry, 2022)
The palladium-catalyzed decarboxylative reactions of phenols and vinyl ethylene carbonate to produce allylic aryl ethers under mild conditions have been established. Adopting an inexpensive PdCl2(dppf) catalyst promotes the efficient conversion of phenols to the corresponding allylic aryl ethers via the formation of a new C-O bond in good isolated yields with acceptable functional group tolerance and operational simplicity. The robust procedure could be completed smoothly by conducting a scaled-up reaction with comparable efficiency to afford the target product.